Smartness Beyond the Network: Water ATMs and Disruptions from below in Mathare Valley, Nairobi. Issue 4 (2nd October 2022) - Guma, Prince K.; Wiig, Alan
ABSTRACT: This article critiques decontextualized notions of smart urbanism by examining the variegated and spontaneous infrastructural configurations stemming from the deployment of a digital project in an informal urban setting. We offer an empirical examination of the rollout of water ATMs in Mathare Valley, Nairobi, to highlight three types of "smartness beyond the network": first, where water ATMs evidence a smart digital infrastructure that transcends the networked urban water supply; second, where residents, in their adoption and use of water ATMs, unsettle their original operation, in the process driving them further away from their original design through disruptions from below; and third, where persistent manifestations of pre-existing mechanisms exist that are non-state and non-networked and sometimes integrate indicating digital technologies heterogeneous articulations and smartness from below. In sum, we argue for unpacking Southern and alternative visions for smart digital infrastructure, considering that smartness, within diverse urban settings, is informed not just by hegemonic and aspirational articulations of city making, but also by dwellers' context-specific and nonlinear processes of place making.